Social Researchers' Approaches to Research Ethics During the COVID-19 Pandemic: An Exploratory Study. (February 2022) - Surmiak, Adrianna; Bielska, Beata; Kalinowska, Katarzyna
The global COVID-19 pandemic and quarantine/distancing measures have forced researchers to cope with a new situation. This paper aimed to analyze how the pandemic and its associated constraints have affected social researchers' approach to research ethics. Drawing on an online qualitative survey with 193 Polish social researchers conducted in April and May 2020, we distinguished three approaches: nothing has changed, opportunity-oriented, and precautionary . According to the first, the pandemic was not regarded as a situation that required additional reflection on ethical issues or changes in research approaches. By contrast, the other two were based on the assumption that the pandemic affected research project ethics. The difference was in the assessment of changes in the area of ethics. The pandemic presented an opportunity and a threat to the ethicality of research, respectively. We discuss the implications of all three approaches for research and education.